Pengaruh Return on Asset dan Return on Equity serta Net Profit Margin terhadap Harga Saham Indeks Lq45 di Bursa Efek Indonesia - Junaidi, Junaidi; Cipta, Wayan (Universitas Pendidikan Ganesha, 2021)
This study aims to examine about the effect of return on asset, return on equity and net profit margin on share price simultaneously and partially in LQ-45 companies. The subjeck of this research is the LQ-45 company and the research objects are return on assets, return on equity, net profit margin and stock price. Data were collected by recording documents and analyzed by multiple linear regression analysis. The results show that (1) there is a simultaneous significant effect of return on asset, return on equity and net profit margin on stock price of 71.8%, (2) there is partially positive significant effect of return on assets on stock price amounting to 52.1%, (3) there is partially positive significant effect of return on equity on stock price of 26.0%, (4) there is partially positive and significant effect on net profit margin on stock price of 52.7%